Advances in the drug therapies of acute myeloid leukemia (except acute promyelocytic leukemia) - Lin M; Chen B (Dove Medical Press, 2018)
Min Lin, Baoan Chen Department of Hematology and Oncology, Zhongda Hospital, School of Medicine, Southeast University, Nanjing, People’s Republic of China Abstract: Acute myeloid leukemia (AML) is a heterogeneous hematologic malignancy, characterized by the clonal expansion of myeloid blasts in the peripheral blood, bone marrow, and/or other tissues. The new drugs used for treating AML are facing a big challenge, and the candidates include cytotoxic drugs, targeted small-molecule inhibitors, and monoclonal antibodies. In recent years, active research has focused on several new agents for including them in the large antileukemic drug family. This review aims to introduce some of these new drugs and highlights new advances made in the old drugs, mainly in the last 5 years. Keywords: acute myeloid leukemia, new drug therapies, refractory/relapsed AML, 2017 NCCN guideline